Dividend Payments and Cross-country Differences in the Choice of Dividend - Belousova, Alina A.; Gurianov, Pavel A.; Melnichuk, Aleksandr V.; Vinichenko, Mikhail V.; Duplij, Elena V. (International Journal of Economics and Financial Issues, 2016)
One of the hallmarks of good corporate governance is a well built and complies with the dividend policy, taking into account the interests of both the majority and minority shareholders, companies need to preserve and accrued competitive position in the market. Companies that pay dividends pay attention to credit rating agencies. A comparative analysis of the main indicators of dividend in the emerging markets of Russia and Poland with the performance of the developed markets of France and Germany. In the Russian data tested Lintner model describes well the trajectory of dividend payments in the developed markets. Isolated set of financial results of Russian companies that have an impact on their decision to pay dividends on the selected size of payments, revealed differences in dividend-making companies that have carried out cross-listing from making dividend companies whose shares are listed in Russia. This paper discusses mainly observed the company's decision to pay or not to pay dividends and the establishment of the amount of dividends in each year separately. For a description of such decisions used the term “dividend of choice” or “dividend decisions”. It also shows that dividend decisions of companies can vary significantly in different countries. Keywords: Financial capital structure, dividend policy, financial markets, dividend option JEL Classifications: G32, F62, D53